Lingonberry (Vaccinium vitis-idaea L.) Interact With Lachnum pygmaeum to Mitigate Drought and Promote Growth - Lou, Hu; Guo, Chao; Fan, Baozhen; Fu, Rao; Su, Heng; Zhang, Jie; Sun, Long (Frontiers in Plant Science, 2022)
The application of Ericoid mycorrhizal (ErM) fungi is considered to be an important strategy for increasing plant yield and drought resistance. In this study, we isolated and identified two ErM fungi that can promote the growth of lingonberry. We tried to understand the potential of these two ErM fungi to promote the growth of lingonberry and the strategies to help plants cope with water shortage. The use value of ErM fungi was evaluated by inoculating Oidiodendron maius FC (OmFC) or Lachnum pygmaeum ZL6 (LpZL6), well-watered (WW) and severe drought stress (SDS). The results showed that the mycelium of LpZL6 was denser than that of OmFC, and both ErM fungi significantly increased the biomass of lingonberry stems and roots. They also significantly increased the chlorophyll content by 65.6% and 97.8%, respectively. In addition, inoculation with LpZL6 fungi can improve drought resistance, promote root growth and increase root wet weight by 1157.6%. Drought reduced the chlorophyll content and soluble sugar content of lingonberry but increased significantly after inoculation with LpZL6. Inoculation with LpZL6 decreased lingonberry’s MDA (malondialdehyde) content but increased the SOD (superoxide dismutase) activity. Overall, these results indicated that the successful coexistence of ErM fungi and lingonberry alleviated the adverse effects of drought stress through higher secondary metabolites and photosynthetic pigment synthesis.